Soil fungal and bacterial communities are altered by the incorporation of leaf litter containing a fungal endophyte. (27th May 2022) - Jin, Yuanyuan; Wei, Xuekai; White, James F.; Chen, Taixiang; Li, Xiuzhang; Chen, Zhenjiang; Li, Chunjie
Abstract: Litter decomposition plays a key role in nutrient cycling across ecosystems. The presence of Epichloë endophytes in grass plants affects litter decomposition. The overall effects of leaf litter containing Epichloë endophytes on the chemical and biological properties in non‐rhizosphere soils have not previously been examined. The current study is aimed to understand the effect of direct incorporation of leaf litter from Epichloë endophyte‐infected perennial ryegrass ( Lolium perenne ) on soil chemical characteristics, and fungal and bacterial biodiversity. Firstly, fresh leaf litter of the endophyte Epichloë festucae var. lolii ‐infected (E+) and endophyte‐free (E−) L. perenne were incorporated into the soil, and then samples were collected from E+ and E− litter incorporated soil at T0, T1, T2 and T3 (0, 120, 240 and 360 days) for chemical and sequencing analyses. The Epichloë ‐containing leaf litter incorporation changed the soil microbial environment by enhancing the soil organic carbon (SOC), total nitrogen (TN), total phosphorus, NH4 + –N and NO3 − –N contents, and acidifying soil pH. The endophyte had stronger effects on soil bacteria than soil fungi when the litter was determined with and without the endophyte. Litter containing the Epichloë endophyte significantly increased the absolute abundance of the 16S rRNA gene and relative abundances of the Actinobacteria, Nitrospirae and Gemmatimonadetes, while significantly decreasing the relative abundances of the Planctomycetes and Rokubacteria and the diversity in soil bacteria community. There was no significant effect of endophyte‐containing leaf litter incorporation on the absolute abundance and diversity of the soil fungal community except the increment in the relative abundance of Rozellomycota. Soil pH and the SOC‐to‐TN ratio (C:N) were the main factors influencing the soil bacterial community, and the presence of E. festucae var. lolii was directly and positively related to the soil bacterial diversity. The current study established that Epichloë endophyte‐infection altered the abundance and diversity of the soil bacterial community by affecting leaf litter quality and increasing soil chemical properties after litter incorporation. Highlights: Soil microbial habitat was changed by leaf litter with Epichloë endophyte incorporation. Litter containing endophytes increased the absolute abundance of the 16S rRNA gene. Epichloë endophytes altered the diversity of bacteria during litter incorporation. The response of soil bacteria to a litter containing endophytes was greater than that of soil fungi.